Pengelolaan Konflik Kepentingan di Lembaga Legislatif Prespektif Siyasah Syar’iah - M, Mutmainnah; Pratama, Raffi Farid Amar; K, Kurniati (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In the context of conflicts of interest in legislative institutions, the Islamic legal perspective highlights the moral and ethical principles that underlie the duties of leaders and decision makers. This research explains that integrity, honesty and justice are very important values in making public policies according to Islamic teachings. In this research, what will be studied is what is the perspective of Islamic law in handling and resolving social conflicts? And what are the conflicts of interest in legislative institutions from an Islamic legal perspective? The research method used in this research is a qualitative research method using books, journals and several legal regulations as primary data in this research. In conclusion, the results of this research explain that conflicts in government institutions can be overcome if the implementation adopts sharia values, one of which is transparency. This can prevent conflicts within the Institution.